Interactive effect of dietary protein and dried citrus pulp levels on growth performance, small intestinal morphology, and hindgut fermentation of weanling pigs - Almeida, V. V. [UNESP]; Nunez, A. J. C.; Schinckel, A. P.; Alvarenga, P. V. A. [UNESP]; Castelini, F. R. [UNESP]; Silva-Guillen, Y. V. [UNESP]; Thomaz, M. C. [UNESP] (Amer Soc Animal Science, 2017)
Weanling pigs (n = 108, 21 d of age, 5.82 +/- 0.16 kg initial BW) were assigned to a 2 x 2 factorial arrangement of treatments to evaluate the effects of dietary levels of CP (high-and low-CP diets) and dried citrus pulp (DCP; 0% and 7.5%) on growth performance, small intestinal morphology, and hindgut fermentation. Pigs were blocked by initial BW and allotted to 1 of 9 pens, each containing 3 pigs. The high-CP diets consisted of feeding 20% and 21% CP levels throughout phase 1 (0 to 14 d) and phase 2 (14 to 28 d), respectively. For the low-CP diets, CP levels were reduced by 4% units as compared with the highCP diets in both phases. Crystalline AA were supplied to maintain an ideal AA pattern. Pig BW and pen feed disappearance were recorded weekly. On d 7 and 28 postweaning, 1 pig from each pen was euthanized for collection of small intestinal tissues and digesta from cecum and colon. There were no CP x DCP interactions for growth performance and gut morphology. Although the low-CP diet decreased ADG (P = 0.03) and G: F (P = 0.02) from d 21 to 28 postweaning, overall performance was unaffected by the treatments. On d 7 postweaning, pigs fed the low-CP diet tended to have increased (P = 0.09) crypt depth in the duode-num. Low-CP diets tended to increase (P = 0.06) crypt depth and reduce (P = 0.08) villus: crypt ratio in the jejunum on d 7. Dietary treatments did not affect ileal morphology. On d 7 postweaning, low-CP diets tended to reduce (P = 0.09) cecal total VFA, whereas dietary DCP inclusion tended to decrease (P = 0.07) colonic propionate. Including 7.5% DCP to the diet decreased (P < 0.05) colonic isovalerate and ammonia N concentrations on d 7 only for pigs fed the low-CP diet. On d 28 postweaning, DCP inclusion in low-CP diets decreased (P < 0.05) butyrate, isovalerate, and valerate concentrations in the cecum, as well as isovalerate, valerate, and ammonia N concentrations in the colon. Including 7.5% DCP to the diet increased (P < 0.05) acetate: propionate ratio in the hindgut on both d 7 and 28 postweaning only for pigs fed the high-CP diet. Lactate concentration was unaffected by the treatments. These results indicate that feeding low-CP AA-supplemented diets did not compromise overall growth performance, but slightly increased damage in the gut morphology of weanling pigs. Moreover, adding 7.5% DCP to lowCP AA-supplemented diets shifted the fermentation pattern in the hindgut of weanling pigs by decreasing protein fermentation metabolites.
Keywords: fermentable carbohydrate; nursery pig; protein fermentation; weaning